Prevalence of Colon Polyps Detected in Patients did colonoscopy inKarbala gastroenterology center - alturfy, hameed (Karbala Journal of Medicine, 2020)
Objective —.Colonic polyp is a relatively common benign condition (that could transform to malignancy) mainly affecting middle-aged adults. Data from the literature reveal very limited information about its prevalence in Karbala, Iraq. The objective of this study is to predict the prevalence and location of colon polyps detected via the endoscope among population at riskand todetermine its variation based on age and gender. Methods—This is a cross sectional screening study. It was performed in Karbala, Iraq.Colonoscopy data were retrospectively collected from the endoscope unit records system from Al-Hussein Medical City and Al-Kafeel Hospital in Karbala during the period from September, 2012 through May, 2016. A total of 1380 patients' colonoscopy reports (810 males and 570 females) were collected, patients' age range (4-67 years). All patients were suffering bleeding per rectum and/or chronic diarrhea who received colonoscopy screening. The prevalence of anypolyp ≥10 mm was recorded for age and gender. Results—Colon polyps were found in 227/1380 patients (16.44%); 125/810 (15.43%)in males and 102/570 (17.89%) in females. There was no significant difference between prevalence of polyps ≥10 mm between males and females, (adjusted OR 1.02; 95% CI 0.76–1.13).The highest prevalence rate of colonic polyp was 11.1% in the age group 41-45 yrs followed by age group 36-40 years 10.13%, (p = 0.15; adjusted OR 0.99; 95% CI 0.79–1.06). Rectum is the most commonly affected site (41.84%) followed by sigmoid colon (22.44%).Multiple polyps in different sites 13.65%. Multiple polyps in the same colon region 12.33% Conclusion—Theprevalence of colon polyps ≥10 mm in population at risk during the study period was about 16.44%in Karbala, Iraq with no significant gender variation. In addition, the highest prevalence rate was in patients' age group 41-45 years and the most common affected site is rectum followed by sigmoid colon.